2016
DOI: 10.5116/ijme.56e5.491a
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of web-based and face-to-face interviews for application to an anesthesiology training program: a pilot study

Abstract: ObjectivesThis study compared admission rates to a United States anesthesiology residency program for applicants completing face-to-face versus web-based interviews during the admissions process. We also explored factors driving applicants to select each interview type.MethodsThe 211 applicants invited to interview for admission to our anesthesiology residency program during the 2014-2015 application cycle were participants in this pilot observational study. Of these, 141 applicants selected face-to-face inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
167
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(170 citation statements)
references
References 25 publications
3
167
0
Order By: Relevance
“…Both studies found that applicants appreciated the convenience and cost-saving benefits of webbased interviews. Vadi et al directly compared in-person versus web-based interviews in a pilot study of 211 candidates who applied for an anesthesiology residency [14]. In the study, 127 applicants (75.1%) completed face-to-face interviews and 42 (24.9%) completed web-based interviews.…”
Section: Covid-19 and Fellowship Interviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both studies found that applicants appreciated the convenience and cost-saving benefits of webbased interviews. Vadi et al directly compared in-person versus web-based interviews in a pilot study of 211 candidates who applied for an anesthesiology residency [14]. In the study, 127 applicants (75.1%) completed face-to-face interviews and 42 (24.9%) completed web-based interviews.…”
Section: Covid-19 and Fellowship Interviewsmentioning
confidence: 99%
“…The researchers found that the type of interview did not influence which applicants were selected for admission to the residency program. Vadi and team concluded that web-based interviews are a viable alternative to traditional interviews [14].…”
Section: Covid-19 and Fellowship Interviewsmentioning
confidence: 99%
“… 19 The Department of Anesthesiology at Loma Linda University School of Medicine observed that the proportion of applicants accepted to residency programs was not affected by the modality of the interview. 9 …”
Section: Introductionmentioning
confidence: 99%
“…In light of the aforementioned environmental, nancial and opportunity costs associated with faceto-face interviews, some programs have attempted to transition towards video-based interviewing with differing results 7 -11 . In a study of applicants given the option between video-based or face-to-face interviews, video-based interviews were primarily chosen when there were nancial limitations, travel concerns, or interview con icts 11 . While video-based interviews were found to be a viable alternative to face-to-face interviews in a pilot study of medical students applying to the anesthesiology residency program, other studies view video-based interviews as an effective adjunct rather than a replacement to the traditional face-to-face interview 9,11 .…”
Section: Introductionmentioning
confidence: 99%
“…In a study of applicants given the option between video-based or face-to-face interviews, video-based interviews were primarily chosen when there were nancial limitations, travel concerns, or interview con icts 11 . While video-based interviews were found to be a viable alternative to face-to-face interviews in a pilot study of medical students applying to the anesthesiology residency program, other studies view video-based interviews as an effective adjunct rather than a replacement to the traditional face-to-face interview 9,11 . Barriers to transitioning to video-based interviews have mainly been due to concerns of less rapport and being less effective in allowing applicants to represent themselves 9 .…”
Section: Introductionmentioning
confidence: 99%